Nonverbal communication across disciplines - Poyatos, Fernando (John Benjamins, 2002)
This volume, based on the first two, identifies the verbal and nonverbal personal and environmental components of narrative and dramaturgic texts and the cinema - recreated in the first through the 'reading act' according to gaze mechanism and punctuation - and traces the coding-decoding processes of the characters' semiotic-communicative itinerary between writer-creator and reader-recreator. In our total experience of a play or film we depend on the sensory and intellectual relationships between performers, audience and the environment of both, in a temporal dimension starting on the way to the theater and ending as one comes out. Two chapters discuss the speaking face and body of the characters and the explicit and implicit (at times 'unstageable') paralanguage, kinesics and quasiparalinguistic and extrasomatic and environmental sounds in the novel, the theater and the cinema, and the functions of personal and environmental silences. Another shows the functions, limitations and problems of punctuation systems in the creative-recreative processes and how a few new symbols and modifications would avoid some ambiguities. The stylistic, communicative and technical functions of nonverbal repertoires in the literary text are then identified as enriching critical analysis and offering new perspectives in translation. Finally, 'literary anthropology' (developed by the author in the 1970s) is is presented as an interdisciplinary area based on synchronic and diachronic analyses of the literatures of the different cultures as a source of anthropological and ethnological data. Nearly 1200 quotes from 170 authors and 291 works are added to those in the first two volumes.